PENGEMBANGAN MEDIA PEMBELAJARAN PTERIDOPHYTA BERBASIS HERBARIUM - Salwa Rezeqi; Dina Handayani (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the feasibility of herbarium media used in the learning process on Pterydophyta material. This research is a mining study that refers to Dick and Carey. The sample used is 50 students taken by random sampling. The data obtained were analyzed descriptively quantitatively. Herbarium media is validated by media experts with 89.07% percentage with very reasonable criteria and validation by material experts with 86.46% value with media criteria produced also very feasible. After the improvement in accordance with the validator's suggestion and then continued product trial to students with a percentage value of 85.27% indicating that the herbarium media product produced is very good.Keywords: learning media, herbarium, Pterydophyta